2018
DOI: 10.1002/cam4.1428
|View full text |Cite
|
Sign up to set email alerts
|

Albumin‐to‐fibrinogen ratio as a promising biomarker to predict clinical outcome of non‐small cell lung cancer individuals

Abstract: Chronic inflammation is one of the critical causes to promote the initiation and metastasis of solid malignancies including lung cancer (LC). Here, we aimed to investigate the prognostic roles of albumin (Alb)‐to‐fibrinogen (Fib) ratio (AFR), Fib and Alb in LC and to establish a novel effective nomogram combined with AFR. Four hundred twelve LC patients diagnosed between February 2005 and December 2014 were recruited in this prospective study. The prognostic roles of AFR, Fib, Alb, neutrophil‐to‐lymphocyte rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
68
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 30 publications
6
68
0
Order By: Relevance
“…Cho et al [15] in the study that was assessed Recently, the association of fibrinogen and albumin started to be investigated in coronary artery disease and in many cancer cases. In many cancer diseases such as hepatocellüler ca [17], breast ca [19], non-squamöz eausofagial ca [20] and lung ca [21], fibrinogen to albumin ratio was calculated and high FAR was associated with bad prognosis. In one of the rare studies on the rate of fibrinogen albumin in coronary artery disease, Karahan et al [22] showed that FAR is significantly related to SYNTAX Score in predicting the severity of CAD in patients with ST-elevation myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Cho et al [15] in the study that was assessed Recently, the association of fibrinogen and albumin started to be investigated in coronary artery disease and in many cancer cases. In many cancer diseases such as hepatocellüler ca [17], breast ca [19], non-squamöz eausofagial ca [20] and lung ca [21], fibrinogen to albumin ratio was calculated and high FAR was associated with bad prognosis. In one of the rare studies on the rate of fibrinogen albumin in coronary artery disease, Karahan et al [22] showed that FAR is significantly related to SYNTAX Score in predicting the severity of CAD in patients with ST-elevation myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a dynamic alteration of circulating acute phase reaction proteins, such as brinogen (Fib), albumin (Alb) and pre-albumin (pAlb), has been implicated in prolonged in ammation and disease elevation. In fact, previous studies have demonstrated that ratios of Alb to Fib (AFR) and Fib to pAlb (FPR) are independent markers for predicting clinical outcomes in many kinds of solid malignancies, including non-small cell lung cancer [16], esophageal, hepatocellular and gastric cancers [17][18][19]. In our previous study, we demonstrated that preoperative FPR is closely associated with chemoresistance and outcomes of metastatic CRC [20].…”
Section: Introductionmentioning
confidence: 92%
“…Actually, some investigators have reported that pretreatment AFR could serve as a promising biomarker to predict survival in several cancers such as the non-small cell lung cancer (NSCLC), breast cancer, squamous cell carcinoma of esophagus (SCCE) and hepatocellular carcinoma and low AFR predicts poorer survival for cancer patients. [7][8][9][10] Albumin and fibrinogen are both inflammatory and immunological proteins which involve in the initiation, growth and metastasis of tumors. 7 Hence, we hypothesized that circulating AFR could serve as an effective indicator to predict the prognosis and contribute to the formulation of therapeutic strategy for ESCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Albumin and fibrinogen are both inflammatory and immunological proteins which involve in the initiation, growth and metastasis of tumors. 7 Hence, we hypothesized that circulating AFR could serve as an effective indicator to predict the prognosis and contribute to the formulation of therapeutic strategy for ESCC patients.…”
Section: Introductionmentioning
confidence: 99%